2016
DOI: 10.1111/jpc.13210
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes after prelabour rupture of membranes before 24 weeks' gestation

Abstract: Almost one-third of pregnancies complicated by PROM before 24 weeks resulted in pre-viable preterm delivery. In pregnancies continuing to a viable gestation, there remained a significant risk of neonatal mortality and morbidity, primarily due to respiratory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Of these, 38 were selected for full text article review. Finally, 18 articles [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in the review. Figure 1 shows the whole process of study selection, using PRISMA flow diagram [26].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 38 were selected for full text article review. Finally, 18 articles [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] were included in the review. Figure 1 shows the whole process of study selection, using PRISMA flow diagram [26].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, risk factors for neonatal BPD during pregnancy include intrauterine growth restriction and chorioamnionitis [ 24 ]. One study reported that the incidence rate of BPD was higher in cases who experienced pPROM before 31 weeks of gestation than those who did not experience the condition [ 27 ], Another study reported that from among 36 neonates who were born to mothers diagnosed with pPROM before 24 weeks of gestation and who were discharged following delivery, 17 (47%) developed BPD [ 28 ]. Oligohydramnios was found to be a risk factor for BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, risk factors for neonatal BPD during pregnancy include intrauterine growth restriction and chorioamnionitis (21). One study reported that the incidence rate of BPD was higher in cases who experienced pPROM before 31 weeks of gestation than those who did not experience the condition (24), Another study reported that from among 36 neonates who were born to mothers diagnosed with pPROM before 24 weeks of gestation and who were discharged following delivery, 17 (47%) developed BPD (25).…”
Section: Discussionmentioning
confidence: 99%